Investigating the role of an alien baitworm as a consumer in a protected estuarine bay: the case of Diopatra aciculata (Annelida: Onuphidae) in the Knysna Estuary of South Africa - Van Rensburg, Hendre (Stellenbosch : Stellenbosch University, 2025)
Thesis (PhD)--Stellenbosch University, 2025.